From neglect to limelight: Issues, methods and approaches in enhancing sustainable conservation and use of Andean grains in Bolivia and Peru - Rojas, Wilfredo; Valdivia, Roberto; Padulosi, Stefano; Pinto, Milton; Soto, José Luis; Alcócer, Elsa; Guzmán, Lorena; Estrada Zúniga, Rigoberto; Apaza Mamani, Vidal; Bravo, Rosario (kassel university press GmbH, 2023)
Quinoa (Chenopodium quinoa Willd.), cañihua (C. pallidicaule Aellen) and amaranth (Amaranthus caudatus L.) are staple crops for millions of people in the Andes (NATIONAL RESEARCH COUNCIL 1989, HOLLE 1991, JACOBSEN et al. 2003). Their nutritional content (high quality proteins and good micronutrient profile), hardiness, good adaptability to environmental stresses, versatility in use, and rich associated food culture and traditions are among the reasons for their widespread use by the native civilizations of the Andes over millennia. The role of these species as a staple food has however dramatically changed in the last fifteen years due to their poor economic competitiveness with commodity cereal crops, lack of improved varieties or enhanced cultivation practices, drudgery in processing and value addition, disorganized or non-existent market chains as well as a negative image as “food of the poor” (QUEROL 1988, TAPIA et al. 1992, PADULOSI et al. 2003). Less nutritious, but more practical and trendier products made of wheat, maize and rice have been replacing Andean grains in the diets of millions of people across Bolivia, Peru and Ecuador, countries whose history has been intimately linked to the domestication and use of these ancient crops (PEARSALL 1992). The reduced use of Andean grains has been accompanied by the loss of their genetic diversity with important, albeit less obvious, repercussions for the livelihoods of Andean communities in terms of reduced sustainability and resilience of local agricultural systems, wasted opportunities for improving food and nutrition security, impoverishment of local cultures resulting in reduced self esteem and identity of people (BRESSANI, 1993, KRALJEVIC 2006). As with minor millets in South Asia or leafy vegetables in sub-Saharan Africa (ONIANG’O et al., 2006), the case of Andean grains is representative of the limits of the Green Revolution approach, which concentrated its efforts on global commodity crops, missing out hundreds of other valuable species of regional or local importance and of great value to people’s livelihoods (PADULOSI 2008). The recognition that agricultural biodiversity is a strategic asset in people’s lives has promoted over the last fifteen years or so, the rediscovery of those so-called neglected and underutilized species (NUS) crops which, as in the case of Andean grains, have for too long faced marginalization from the Research and Development sector, which has not supported their continued and effective use (PADULOSI and HOESCHLE-ZELEDON 2008). Several projects and collaborative research frameworks at national and international level have been launched in support of NUS, contributing to a re-focussing of needed and deserved attention on these ‘forgotten crops’. To that end, an important role in demonstrating the value of NUS and the development of best practices, methodologies and tools for their use enhancement is being played by the ‘IFAD-NUS Project’, the first UN-supported global effort dedicated solely to the use enhancement of NUS, including quinoa, cañihua and amaranth, tackled through international participatory, multi-stakeholder and multi-disciplinary efforts. This article reports on the work implemented by the project in Bolivia and Peru over the last seven years, highlighting significant approaches, experiences and outputs as well as challenges and experiences during the implementation of the project, which could be valuable lessons for other similar endeavors in support of NUS.